PEMBERHENTIAN SEMENTARA KEPALA DAERAH DAN / ATAU WAKIL KEPALA DAERAH KARENA MELAKUKAN TINDAK PIDANA (TINJAUAN YURIDIS ATAS PASAL 83 UNDANG-UNDANG NO. 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH) (Lex Jurnalica, 2017)
AbstrakThis paper discusses two issues related to the temporary dismissal of the regional head and / or the deputy head of the region for committing a crime under Article 83 of Law no. 23 Year 2014 on Regional Government. First Issue; What is the reason for the temporary dismissal of the regional head and / or deputy regional head under Article 83 of Law no. 23 Year 2014 on Regional Government. Second problem, when the regional head and / or deputy regional head are temporarily suspended from his / her position according to Article 83 of Law no. 23 Year 2014 on Regional Government. Editorial "imprisonment for a minimum of 5 (five) years" in the norm of Article 83 Paragraph (1) of the Act refers to the maximum number of sentences of imprisonment for a maximum of 5 (five) years imprisoned in the criminal section charged to the regional head and / or deputy regional head, and not the number of prison sentences charged by the prosecutor in the demand letters, nor the number of sentences the judge decided.The norm in Article 83 paragraph (1) refers to the criminal sections which contain the threat of imprisonment of the maximum / minimum and maximum / maximum penalty at the same time. Second, the temporary dismissal of the regional head and / or deputy head of the region shall be conducted after the file of the case of the regional head and / or deputy regional head is registered in the court.Â  Â Keywords : Dismissal, regional, a crime Â AbstrakTulisan ini membahas tentangÂ  dua permasalahanÂ  terkait pemberhentian sementara kepala daerah dan/atau wakil kepala daerah karena melakukan tindak pidana menurut Pasal 83 Undang-Undang No. 23 Tahun 2014 Tentang Pemerintahan Daerah.Â  Permasalahan Pertama; Bagaimana alasanÂ  pemberhentian sementaraÂ  kepala daerah dan/atau wakil kepala daerah menurut Pasal 83 Undang-Undang No. 23 Tahun 2014 Tentang Pemerintahan Daerah.Â  Permasalahan Kedua,Â  kapan kepala daerah dan/atau wakil kepala daerah diberhentikan sementara dari jabatannya menurut Pasal 83 Undang-Undang No. 23 Tahun 2014 Tentang Pemerintahan Daerah. Redaksi â€œ pidana penjaraÂ  paling singkat singkatÂ  5 (lima) tahunâ€ dalam norma Pasal 83 ayat (1) Undang-undang tersebut menunjuk pada jumlah ancaman hukuman pidana penjara paling singkat atau paling lama 5 (lima) tahun yang disebutkan dalam pasal pidana yang didakwakan kepada kepala daerah dan/atau wakil kepala daerah, dan bukan jumlah hukuman pidana penjara yang dituntut oleh penuntut umum dalam surat tuntutan, dan bukan pula jumlah hukuman yang diputuskan hakim. Norma dalam Pasal 83 ayat (1)Â  tersebut menunjuk pada pasal-pasal pidana yang memuat ancaman hukuman pidana penjara paling singkat/minimal dan paling lama/maksimal sekaligus.Â  Kedua,Â  pemberhentian sementara kepala daerah dan/atau wakil kepala daerah tersebutÂ  dilakukan setelah berkas perkara kepala daerah dan/atau wakil kepala daerah diregister di pengadilan.Â Â Kata kunci : pemberhentian, kepala daerah, tindak pidana